Troškūnų vienuolyno biblioteka - Pacevičius, Arvydas (Knygotyra, 1997)
In the former territory of the Grand Duchy of Lithuania, which was incorporated into the Russian Empire in 1795, the Catholic cloisters had numerous and valuable book collections. The Troškūnai (now in the district of Anykščiai in East Lithuania) cloister’s Library of bernardines was founded in 1696 and secularized in 1864 following Tsarist repressions. The collections of the library increased with the help of donations from aristocrats and monks, also thanks to the chief of the Bernardine Province of Lithuania, Aleksandras Butkevičius, who initiated a catalogue of this library written in 1782. This catalogue and other historical sources certify that there were 703 volumes of books in the Troškūnai library in 1784, 1255 volumes in 1800, and 1501 volumes in 1841. The analysis of the catalogue showed that no less than 54-56 percent of this collection was religious, scholastic, or polemic literature. However, gifts and the need to maintain books for the Troškūnai gymnasium (a secondary school administered by the monks) were reasons why the library also collected scientific literature and classical antiquities. This book collection was predominantly in Latin and Polish, but towards the end of the 18th century, the share of West-European and Lithuanian languages began to increase. For example, there were 7 "Lithuanian-Latin-Polish" dictionaries by Konstantinas Sirvydas and 14 other books in the Lithuanian language. The Library of the Troškūnai cloister was modern, as more than 90 percent of the collection consisted of 18th-century issues; on the other hand, it reflected the increasing role of books in Lithuanian society during this period. The original sign in the Library of Troškūnai was left by the famous Lithuanian preacher of the bernardines, Kiprijonas Lukauskas (Cyprianus Lukowski). He presented a heraldic book by Andrzej Kuropatnicki, issued in Warsaw in 1789. The facts mentioned above allow us to conclude that the quantity and character of the Troškūnai book collection depended on internal (regulation of the Bernardine Order, the leader’s personality) and external (the program of benefactors, the book market, government politics) circumstances. On the other hand, Enlightenment ideas were accepted and adopted in Lithuania, and the confessional intelligentsia participated in this process.